Parents', Teachers', and Learners' Perceptions Regarding the Use of the IsiNdebele-Developed Scientific Language Register to Teach Natural Sciences - Ntuli, Thuli Gladys (Studies in Learning and Teaching, 2025)
Researchers indicate that learners who are learning through a language that is not their own experience greater difficulty attaining the same level in science education than those learners whose home language is the same as the Language of Learning and Teaching (LoLT). This shows a dire need for the development and application of scientific language registers in indigenous languages. In this qualitative interpretative case study, the researcher aimed to elucidate the perceptions of parents, learners, and teachers on the use of the developed IsiNdebele scientific register to teach natural sciences. This paper was guided by the following research question: What are the stakeholder's perceptions on the development and use of the isiNdebele scientific language register to teach Natural Sciences? Purposeful sampling was used to select the participants of this study: teachers, learners, and parents (stakeholders). The data for this paper was collected through interviews and observations. The results of the study reveal that isiNdebele is still underdeveloped as it lacks scientific terms and reveals different perceptions held by stakeholders on the use of the developed isiNdebele scientific language register to teach Natural Sciences. With the numerous research findings on the benefits of using indigenous languages and the results of this study, it is recommended that stakeholders re-consider their perceptions on the use of indigenous languages and scientific language registers be developed in indigenous languages as the use of these languages has proven to yield meaningful learning.